Volatile Components of the Leaves of Vitex simplicifolia Oliv. - OUOBA, A.M.; KOUDOU, J.; SOME, N.; GUISSOU , I.P.; CHALCHAT, J.C. (Asian Journal of Chemistry, 2010)
The composition of the essential oil from the leaves of Vitex simplicifolia Oliv. were studied by capillary gas chromatography. The analysis using a combination of retention indices and combined GC/MS led to the identification of 52 components. The essential oil contains mainly mono terpenoids (71.02 %) out of which 64.70 % are monoterpene hydrocarbons and some sesquiterpene hydrocarbons (22.03 %). The major constituent was myrcene (53.50 %).